Betulinic Acid: Recent Advances in Chemical Modifications, Effective Delivery, and Molecular Mechanisms of a Promising Anticancer Therapy. (29th December 2015) - Ali‐Seyed, Mohamed; Jantan, Ibrahim; Vijayaraghavan, Kavitha; Bukhari, Syed Nasir Abbas
Abstract : An important method of drug discovery is examination of diverse life forms, including medicinal plants and natural products or bioactive compounds isolated from these sources. In cancer research, lead structures of compounds from natural sources can be used to design novel chemotherapies with enhanced biological properties. Betulinic acid (3β‐hydroxy‐lup‐20(29)‐en‐28‐oic acid or BetA) is a naturally occurring pentacyclic triterpene with a wide variety of biological activities, including potent antitumor properties. Non‐malignant cells and normal tissues are not affected by BetA. Because BetA exerts its effects directly on the mitochondrion and triggers death of cancerous cells, it is an important alternative when certain chemotherapy drugs fail. Mitochondrion‐targeted agents such as BetA hold great promise to circumvent drug resistance in human cancers. BetA is being developed by a large network of clinical trial groups with the support of the U.S. National Cancer Institute. This article discusses recent advances in research into anticancer activity of BetA, relevant modes of delivery, and the agent's therapeutic efficacy, mechanism of action, and future perspective as a pipeline anticancer drug. BetA is a potentially important agent in cancer therapeutics. Abstract : Betulinic acid (BetA) is a naturally occurring pentacyclic triterpene with a wide variety of biological activities and proven as promising agent for cancer therapy and have shown selectivity for cancer cells and a remarkable lack of toxicity for human cells. It targets mitochondria, may be particularly useful in therapy‐resistant cancer cells and refractory tumors.